Implementation of the Levenshtein Distance Algorithm and the Regular Search Expression Method for Detecting Typors in Javascript - Mu’alif Lihawa; Anggit Dwi Hartanto; Norhikmah Norhikmah; Donni Prabowo; Ika Nur Fajri; Wiwi Widayani (Sistemasi: Jurnal Sistem Informasi, 2023)
Typing is an activity to write an article in printed form that has been assembled by a typewriter. With the rapid development of the times, typewriters were replaced by computers because they were efficient in making writing or text. a text or writing that is easy to understand in conveying information does not have word mistakes that result in unclear information being conveyed. In word processing applications such as Microsoft Office Word, it has the word suggestions and autocorrect word features which are very useful in checking an article where there are word errors in the writing. This research develops a javascript library to detect typo errors for writing wrong words and recommends the right words to change the wrong words. This study uses the Levenshtein Distance Algorithm and the Regular Search Expression method. The results of this study were successfully applied to the word recommendation feature in the library with an accuracy value of 50% and a precision level of 5%.